The interactive pedological-hydrological processes and environmental sensitivity of a tropical isolated wetland in the Brazilian Cerrado - Furlan, Lucas Moreira [UNESP]; Rosolen, Vania [UNESP]; Moreira, César Augusto [UNESP]; Bueno, Guilherme Taitson; Ferreira, Manuel Eduardo (Springer Nature, 2021)
In seasonal flooding isolated wetlands, the degree of wetness suggests a close synergy between soil processes, landscape evolution and hydrology along space and time. Until now, that subject has received insufficient attention despite natural wetlands supply essential environmental services to society and are surrounded by intensive agriculture that uses agrochemicals and fertilizers in their management. The objectives of this study were to propose an infiltration architecture model based on local surface and subsurface water-fluxes in isolated wetland embedded in lateritic plateau covered by savanna and qualify the environmental sensitivity as an area of aquifer recharge. Grain size, soil bulk density, and hydraulic conductivity were determined in five profiles in a soil catena. Unmanned Aerial Vehicle high-resolution images were obtained to generate a digital elevation model and discriminate areas with different vegetation, water accumulation, and environmental sensitivity. Electrical tomography was performed to unveil the soil architecture and infiltration. The soils (Plinthosols) developed on aquic conditions determine the linkage between the surface–subsurface hydrodynamics with the soil's physical properties. We have identified vertical and lateral water-flows in the soil architecture. Vertical flow occurs exclusively at the center, where the wetland is characterized as a recharge zone. Lateral flow towards the borders characterizes a discharge zone. The recharge zone is a depression surrounded by crops; therefore, it is a point of high environmental sensitivity. This hydrodynamic model is essential to support studies related to the dispersion of contaminants since soybean agriculture dominates the whole area of well-drained soils in the Brazilian Cerrado.
Keywords: Aerial photogrammetry; Aquic soil; Aquifer recharge; Bulk density; Hydraulic conductivity; Resistivity